ASSESSMENT OF FACTORS HINDERING MARKETING AMONG SMALLHOLDER VEGETABLE COOPERATIVE FARMERS IN POLOKWANE MUNICIPALITY, LIMPOPO PROVINCE, SOUTH AFRICA - Isaac Oluwatayo; Piletso Sebetha; Ayodeji Ojo (Mesopotamia Journal of Agriculture)
The South African agricultural sector plays an important role in creating jobs, alleviating food insecurity and poverty, and contributes to exports. Agricultural commodities from smallholder farmers are often lost after production due to numerous marketing constraints which make it challenging for smallholder farmers to survey full lucrative markets. This, among other challenges, reduces smallholder farmers’ motivation to participate in formal (commercial) or lucrative markets. The study examined factors hindering marketing among smallholder vegetable cooperative farmers in the Polokwane Municipality. Data used were collected through structured questionnaire from a random sample of one hundred and twenty smallholder cooperative vegetable farmers. Descriptive statistics, the Marketing Hindrance Index and Tobit model were employed as analytical tools to accomplish the objectives of the study. Results of the data analysis revealed that some of the factors hindering marketing among smallholder vegetable cooperative farmers include source of water and types of vegetables grown. The result of Tobit regression analysis revealed that access to credit, access to reliable information about marketing, age, access to storage and farming experience in years were significant variables influencing marketing.In view of the research findings, the study recommends encouragement of youth participation in agriculture, improved access to agricultural information and formal market access and enabling accessibility through the development of better infrastructure as critical to enhancing marketing in the study area.